2021
DOI: 10.3390/ijerph182312759
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Influencing Factors on the Hollowing of Traditional Villages—Taking 2645 Villages from the Chinese Traditional Village Catalogue (Batch 5) as an Example

Abstract: With the rapid development of urbanization and modernization, the population of traditional villages migrates into surrounding areas, causing the hollowing of traditional villages. The disintegration of China’s traditional village means the loss of historical memory and cultural characteristics of ethnic regions, seriously endangering the country’s cultural heritage. To better understand the hollowing phenomenon, this study analyzed 2645 villages from the Chinese traditional village catalogue (Batch 5) and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In addition, our study also found that BRC among older people was lower than BOC both in urban and rural areas. According to the definition of BRC and BOC, it means that rural and urban areas were facing the dilemma of community or village hollowing out ( 45 ). Because there is less social participation and lacking organizations/groups that could provide community public services such as medical services and cultural services for older people ( 46 ), which may make them feel less BRC than BOC subjectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study also found that BRC among older people was lower than BOC both in urban and rural areas. According to the definition of BRC and BOC, it means that rural and urban areas were facing the dilemma of community or village hollowing out ( 45 ). Because there is less social participation and lacking organizations/groups that could provide community public services such as medical services and cultural services for older people ( 46 ), which may make them feel less BRC than BOC subjectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the proposal of China's rural revitalization strategy has garnered increasing attention towards the preservation and rejuvenation of villages [19,20]. Scholarly focus has primarily centered around the design of residential buildings [21], spatial distribution in settlements [22], and the development of village tourism [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Rural revitalization is a key policy that was recently proposed by the Chinese government for supporting rural sustainable development [ 31 , 32 ], which is improving the rural living environment and enhancing the rural economy. Nowadays, research related to rural revitalization focuses mainly on rural e-commerce development [ 33 ], idle rural residential land [ 34 ], land consolidation [ 35 ], protection and inheritance of ancient villages [ 36 , 37 ], and rural tourism [ 38 , 39 ]. Rural tourism has become an essential measure of rural revitalization; however, a more comfortable outdoor environment could attract more tourists.…”
Section: Introductionmentioning
confidence: 99%